Structural tuning of Zn(ii)-MOFs based on pyrazole functionalized carboxylic acid ligands for organic dye adsorption. Issue 36 (12th August 2020) - Liu, Xiao-Ting; Chen, Si-Si; Li, Si-Miao; Nie, Hong-Xiang; Feng, Yao-Qing; Fan, Yi-Ning; Yu, Mei-Hui; Chang, Ze; Bu, Xian-He
Abstract : Two Zn(ii )-MOFs based on pyrazole functionalized carboxylic ligands have been constructed, which exhibit favorable selective adsorption of organic cationic dyes. Abstract : Two metal–organic frameworks, {(NH2 Me2 )[Zn(Pycia)]} n (MOF-1 ) and {(NH2 Me2 )[Zn2 (Pycia)(PBA)]} n (MOF-2 ), have been synthesized based on pyrazole functionalized carboxylic acid ligands for organic dye adsorption. The enlarged pore dimension of MOF-2 suggests the advantage of additional linear auxiliary ligand for the structure tuning of the MOFs. Furthermore, the anionic frameworks of the MOFs endow them with size selective adsorption toward different cationic organic dyes.